Diversity in Biosynthetic Pathways of Galactolipids in the Light of Endosymbiotic Origin of Chloroplasts - Sato, Naoki; Awai, Koichiro (Frontiers in Plant Science, 2016)
Cyanobacteria and chloroplasts perform oxygenic photosynthesis, and share a common origin. Galactolipids are present in the photosynthetic membranes of both cyanobacteria and chloroplasts, but the biosynthetic pathways of the galactolipids are significantly different in the two systems. In this minireview, we explain the history of the discovery of the cyanobacterial pathway, and present a probable scenario of the evolution of the two pathways.